Analysis of the translation of cultural terms from English into Bahasa Malaysia of Enid Blyton's stories / Azura Azlee - Azura , Azlee (2014)
In the translation field, it is very important to be able to produce a translated text that sustained the author's intended messages as close as possible. The task gets more challenging when the target readers of the translated texts are children as there are not only linguistic capability limits that have to be considered, but also the geographical aspects, moral and societal values of the society and religion that were upheld by the young target readers. With these issues in mind, a study on the translation procedures used to translate a popular English fairy-tales into Bahasa Malaysia was carried out. English and Bahasa Malaysia are two languages that come from two different language families that contribute towards two contrasting cultural views as a result of differing world views. As such, the focus of this study is on the translation procedures used to translate culture-related items available in the source text. A comparison is made between Enid Blyton's The Fairies' Shoemaker and Other Stories and its Bahasa Malaysia translation in Landak Yang Cuai dan Lain-lain Cerita. The observations and discussions is focused on the percentage of success of the translator's chosen translation procedures in sustaining or distorting the author's intended message from the source text. The study found that the translator's choice of translation procedures failed to sustain the author's intended messages from the source text as a result of cultural differences that cannot be managed by the linguistic aspects of Bahasa Malaysia.